INVESTMENT IN RESEARCH AND DEVELOPMENT AND THEIR IMPACT ON ECONOMIC GROWTH (GDP GROWTH) OF BOSNIA AND HERZEGOVINA - Marin, Slobodan; Šušić, Milan (Journal of process management and new technologies, 2021)
By investing in research and develo-pment, Bosnia and Herzegovina can achieve a competitive advantage in the market and play an important role in supporting research and development, because it can facilitate investments through tax policies and measures, cooperation between science, the state and companies, etc. It is important to note that all attempts to support stronger investment in research and development are fully justified, especially if their role is placed in the context of potential growth and technological progress in Bosnia and Herzegovina. However, it is important that incentives are created in a way that not only implies investment growth, but also ensures their efficiency. More plastically, it is not only important how much will be invested in R&D, but also how, that is, what exactly will be invested in. There are a number of theoretical models that also explain a number of empirical studies that examine the impact of R&D investment on economic growth (GDP growth). Such empirical research differs in the selected variables, the type of statistical analysis and the results. The paper presents the application of the model of multiple regression analysis in macroeconomic research using the model of Bosnia and Herzegovina in the period from 2005 to 2019. The research aims to assess the effects of selected macroeco-nomic factors, especially R&D (independent variables) on gross domestic product (depe-ndent variable), and to answer the question whether investment in research and develo-pment (GERD) in Bosnia and Herzegovina is satisfactory?
Keywords: Research and development; gross domestic product; multiple regression linear model; Enter method; determination coefficient